Risk factors for lower limb lymphedema after gynecological cancer treatment: a systematic review - Tina Decorte; Marie Cerckel; George Bou Kheir; Chris Monten; Katrien Vandecasteele; Luc Vanden Bossche; Nele S. Pauwels; Caren Randon (Frontiers in Oncology)
IntroductionAs treatments in gynecological cancer improve, the number of cancer survivors increases, with more patients facing long-term side effects of their treatment. One debilitating side effect is lower limb lymphedema (LLL). Unlike upper limb lymphedema (ULL), diagnosis of LLL remains challenging due to the absence of a clear definition, bilateral presentation complicating comparison, and confusion with post-operative weight changes. This systematic review investigated incidences and risk factors for LLL.MethodsWe systematically searched PubMed, Embase, and CENTRAL databases for articles on LLL following treatment for pelvic gynecological cancer from 1979 to November 2024. Two independent researchers extracted data, based on predefined inclusion and exclusion criteria. We assessed bias using the Risk of Bias in Non-Randomized Studies (ROBINS-I) tool and adhered to PRISMA reporting guidelines.ResultsOur review included 46 studies, with incidence rates varying widely across cancer types: 7.4-55.9% in cervical cancer, 1.2-47% in endometrial cancer, 5.6-30.4% in ovarian cancer, and 10.1-43% in vulvar cancer. Several risk factors for LLL emerged. Notably, lymphadenectomy, the number of removed lymph nodes, radiotherapy, and a body mass index (BMI) exceeding 25 kg/m² were significant risk factors. Surgical technique did not impact LLL risk.ConclusionLLL frequently occurs following gynecological cancer treatments, emphasizing the importance of careful monitoring and proactive management in clinical settings. Overall, the findings highlight the complexity and variability in risk factors for LLL across different gynecological cancers. The significant heterogeneity in study designs, populations, and methodologies underscores the need for standardized approaches in future research to better understand and mitigate the risk of LLL in these patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42020198642.